Kesiapan pengelolaan pajak daerah dalam implementasi UU HKPD pada Kabupaten/Kota di Jawa Timur - Hastanti Agustin Rahayu (Nur Science Institute, 2025)
This study examines the readiness of local tax administration to implement Indonesia’s Law No. 1 of 2022 on Fiscal Relations between the Central and Local Governments (UU HKPD) across regencies and municipalities in East Java Province. It employs a descriptive qualitative design using secondary data from local budget documents (APBD), local regulations, BAPENDA performance reports, and official publications of the Ministry of Finance. Data were analyzed using Miles and Huberman’s interactive model and interpreted through Resource Orchestration Theory (ROT), focusing on how local governments structure, bundle, and leverage organizational resources. The findings show uneven readiness across jurisdictions: about 90% of regencies/municipalities have updated PBB-P2 data, all jurisdictions (100%) use information technology and inter-agency collaboration mechanisms in tax administration, and about 40% have strengthened staff competencies through capacity-building initiatives. Changes in tax rates and NPOPTKP, together with the surcharge (opsen) mechanism, are expected to increase PBB-P2 and opsen revenues, while posing downside risks for BPHTB, parking tax, and MBLB revenues. Theoretically, this study extends ROT to local tax administration and underscores that fiscal reform outcomes depend on local governments’ managerial capacity to strategically orchestrate regulations, data, systems, and human resources.